Creep buckling of 304 stainless-steel tubes subjected to external pressure for nuclear power plant applications - Jo, Byeongnam; Okamoto, Koji; Kasahara, Naoto (Metals, 2019)
The creep-buckling behaviors of cylindrical stainless-steel tubes subjected to radial external pressure load at elevated temperatures-800, 900, and 1000 °C-were experimentally investigated. Prior to the creep-buckling tests, the buckling pressure was measured under each temperature condition. Then, in creep-buckling experiments, the creep-buckling failure time was measured by reducing the external pressure load for two different tube specimens-representing the first and second buckling modes-to examine the relationship between the external pressure and the creep-buckling failure time. The measured failure time ranged from <1 min to <4 h under 99-41% loading of the buckling pressure. Additionally, an empirical correlation was developed using the Larson-Miller parameter model to predict the long-term buckling time of the stainless-steel tube column according to the experimental results. Moreover, the creep-buckling processes were recorded by two high-speed cameras. Finally, the characteristics of the creep buckling under radial loading were discussed with regard to the geometrical imperfections of the tubes and the material properties of the stainless steel at the high temperatures.
Keywords: Creep buckling; Elevated temperature; External pressure; Larson-miller parameter; Visualization